Alpha Lead Oxide (α‐PbO): A New 2D Material with Visible Light Sensitivity. Issue 12 (12th February 2018) - Kumar, Prashant; Liu, Jing; Ranjan, Pranay; Hu, Yaowu; Yamijala, Sharma SRKC; Pati, Swapan K.; Irudayaraj, Joseph; Cheng, Gary J.
Abstract: Even though transition metal dichalcogenides (TMDCs) are deemed to be novel photonic and optoelectronic 2D materials, the visible band gap being often limited to monolayer, hampers their potential in niche applications due to fabrication challenges. Uncontrollable defects and degraded functionalities at elevated temperature and under extreme environments further restrict their prospects. To address such limitations, the discovery of a new 2D material, α‐PbO is reported. Micromechanical as well as sonochemical exfoliation of 2D atomic sheets of α‐PbO are demonstrated and its optical behavior is investigated. Spectroscopic investigations indicate layer dependent band gaps. In particular, even multilayered PbO sheets exhibit visible band gap > 2 eV (direct) which is rare among semiconducting 2D materials. The emission lifetime of multilayer PbO atomic sheets is 7 ns (dim light) as compared to the monolayer which gives 2.5 ns lifetime and an intense light. Density functional theory calculations of layer dependent band structure of α‐PbO matches well with experimental results. Experimental findings suggest that PbO atomic sheets exhibit hydrophobic nature, thermal robustness, microwave stability, anti‐corrosive behaviour and acid resistance. This new low‐cost, abundant and robust 2D material is expected to find many applications in the fields of electronics, optoelectronics, sensors, photocatalysis and energy storage. Abstract : Atomic sheets of α‐PbO, a novel 2D material with visible light sensitivity, are exfoliated micromechanically as well as sonochemically and its applications are demonstrated.